Development of Cellular Communications: Specific Aspects of the GSM Standard - Alimardonov Shokhrukh Erkin o‘g‘li (Miasto Przyszłości, 2025)
Currently, the mobile terminal market is developing, and portable computers based on the technology of connecting to the global network through multifunctional smartphone devices, iPad, iPhone and USB modems are achieving a number of successes in transmitting multimedia information. This is necessary at a time when the scope of use of mobile television, mobile education (m-learning), social networks and mobile information systems is expanding day by day. The results achieved in this work provide a comparative analysis of services in different generations of mobile communications and an assessment of the advantages and disadvantages of providing services in 4G networks, which is important in predicting the further development trends of mobile communications.